Utilização de ß-ciclodextrina no processo de tingimento de malhas de PET com corante disperso - Bezerra, Fabricio Maestá (2012)
In this study we used β-cyclodextrin (β-CD) as auxiliary in dyeing knitted PET fabric with dispersed dyes, adding it directly to the dyebath or as β-CD/dye complex, previously prepared. The dye molecules were modeled using the software Avogadro and MOPAC2012. The dimensions of the dyes were compared with the dimensions of β-CD, seen in literature. The yellow dispersed dye molecule presented the best dimensions for a possible complexation with β-CD, having maximum longitudinal and transverse lengths as 12.11 Å and 5.83 Å, the latter being smaller than the diameter of β-CD, which is approximately 6.5 Å. The complexes β-CD/dye were obtained by two techniques, namely physical mixture and kneading. Analysis by infrared spectroscopy showed evidence of coupling as the overlap of the spectral bands of the dye and β-CD at most of the spectral range, and at the spectral region of 1250-1650 cm-1, it is possible to verify a subtle change in the spectrograms, which may be due to some interaction between the host (β-CD) and the guest molecule (dye). The dyeings with β-CD added directly to the bath were carried out using complete factorial design 23 and analysis of the results was made with the software Expert Designer 7.13. The parameters % dye (1 and 3 %), molar ratio of β-CD:dye (1:1 and 2:1) and dyeing time (90 and 150 minutes) showed influence on the response factor K/S (coloristic intensity). For the three dyes the most influential parameter was the % dye, a common trend observed in dyeing, nonetheless the dispersed yellow dye showed different behavior in relation to the molar ratio parameter β-CD:dye, which contributed with 13.01 % increase in the response variable, while the other dyes have a lower value for the contribution of the response variable analyzing this parameter.The trichromatic coordinates in the space CIElab of the dyeings made with the addition of β-CD directly to the dyebath were analyzed and the luminosity coordinate (L) showed a regular decreasing in all cases, regardless of the dye. The dyeings using the complex β-CD/dye showed different results than conventional dyeing and dyeing adding β-CD directly to the bath. The results obtained with the dispersed yellow dye proved most interesting, the β-CD in this case has greater contribuition for intensity coloristic than the dyeings made with other dyes, disperse blue and red. Dyeings were performed using conventional recipes provided by the textile industry and the chemical industry Sintex Golden Chemistry. The dyeings with β-CD were compared to conventional dyeing and presented coloristic intensity higher than the results obtained with the conventional recipes without β-CD. The effectiveness of β-CD as an auxiliary in dyeing depends on the dimensions of the dye molecules as well as functional groups present in these dyes, some being more favorable candidates as the case of the yellow colorant dispersed, which is an azo dye. Another factor that can improve dyeing is the complexation of dyes, and the two methods of complexation tested, physical mixing and kneading, were effective for dyeing.